12(y+3)=

Simple and best practice solution for 12(y+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(y+3)= equation:


Simplifying
12(y + 3) = 0

Reorder the terms:
12(3 + y) = 0
(3 * 12 + y * 12) = 0
(36 + 12y) = 0

Solving
36 + 12y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + 12y = 0 + -36

Combine like terms: 36 + -36 = 0
0 + 12y = 0 + -36
12y = 0 + -36

Combine like terms: 0 + -36 = -36
12y = -36

Divide each side by '12'.
y = -3

Simplifying
y = -3

See similar equations:

| 1+(-0.4)= | | 100+Y+9=139 | | X-5=7+4X | | p/7=12/5 | | [10x-5]+4=8 | | 6(b-6)=8(b+6) | | h=-16t+104t | | 1-2Inx=0 | | 3/t=8/3 | | 6x-1/y=5 | | 7/11=5/n | | 7/t=11/7 | | 7t=11/7 | | -10+2w=-6 | | -11y+5y=14 | | 6/y=3/7 | | 3+77x=44x+6 | | 32-15x=-18+9 | | 11/10=y/12 | | 4k+33=1-3k | | 8g-5w=4 | | a/10=4/9 | | 4a^9+5=8 | | 7+5y-4=6y+6-2y | | 3*(3-x)=5x+27 | | 7x-42=2x+12 | | 4x+10=-35-5 | | 1j^5-7=12 | | X-10=-4X | | 5b^2-36b=32 | | a+f=10 | | 1k+q=8 |

Equations solver categories